2019
DOI: 10.1002/jrs.5599
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of supercontinuum generation in a photonic crystal fiber for uses in multiplex CARS microspectroscopy

Abstract: Coherent anti‐Stokes Raman scattering (CARS) is a versatile technique for vibrational imaging that can be realized by a simple setup using a single femtosecond laser oscillator. For such a layout, supercontinuum generation in a photonic crystal fiber (PCF) is commonly used to produce a broadband Stokes beam in the so‐called multiplex CARS spectroscopy; accordingly, characterization of the supercontinuum beam is a necessary requirement to perform controlled experiments. In this paper, we first perform simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…The experimental setup used in this work is derived from the one described in detail in Falconieri et al [ 22 ] with some minor modifications, and is shown in Figure 1. Briefly, the pulses emitted at 780 nm by an ultrafast Ti:sapphire oscillator (Coherent MIRA‐900F) operating at 76 MHz rep. rate are divided in two beams by a 50/50 beam splitter, one portion being coupled to a FemtoWHITE CARS® PCF (NKT Photonics) by a 40× objective to provide the SC for the Stokes beam, and the other being used to provide the pump/probe beam.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental setup used in this work is derived from the one described in detail in Falconieri et al [ 22 ] with some minor modifications, and is shown in Figure 1. Briefly, the pulses emitted at 780 nm by an ultrafast Ti:sapphire oscillator (Coherent MIRA‐900F) operating at 76 MHz rep. rate are divided in two beams by a 50/50 beam splitter, one portion being coupled to a FemtoWHITE CARS® PCF (NKT Photonics) by a 40× objective to provide the SC for the Stokes beam, and the other being used to provide the pump/probe beam.…”
Section: Methodsmentioning
confidence: 99%
“…These studies evidence the importance of selecting proper PCF excitation conditions (i.e., laser beam power, wavelength, and chirp) to achieve optimal SC spectral distribution and minimal noise , [14,[18][19][20][21] and therefore better performances for CARS measurements. [17,22] Numerical modelling [13,18,23] can be of help to this aim and has been actually used to simulate the SC generation, proving successful in reproducing the gross features of the experimental SC spectra and to evaluate optical noise, [24,25] even though detailed agreement with experimental data can be obtained at the expense of purposely introduced adjustments of the input parameters. [22] As far as noise and instabilities are concerned, it has been reported that noise in the SC spectra has two components [14,25] : the first, at high frequency, is related to the shot noise and has been widely investigated both theoretically and experimentally, [13,14,16,24,25] and a second, at low frequency, referred to as technical noise, which is due to amplification of the fluctuations of the input pulse characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Falconieri et al [ 102 ] characterized supercontinuum generation in a photonic crystal fiber for use in multiplex Coherent anti‐stokes Raman spectroscopy (CARS) microspectroscopy. Based on their work, they were able to achieve good control over the measurement of vibrational bands by CARS microscopy by means of optimized performances in specific spectral bands.…”
Section: Nonlinear Coherent and Time‐resolved Raman Spectroscopymentioning
confidence: 99%
“…For lots of the potential applications an intense, coherent, broadband, and compact mid-IR supercontinuum light sources are essential 2,[19][20][21] . Supercontinuum light generated from a photonic crystal fiber was used in a typical single-oscillator multiplex coherent anti-Stokes Raman scattering (CARS) step for the measurement of vibrational bands of cyclohexane sample 22 . A photonic-chip based supercontinuum light source was used in the mid-IR gas spectroscopy for the detection of acetylene (C 2 H 2 ) gas 23 .…”
mentioning
confidence: 99%